2021
DOI: 10.31557/apjcp.2021.22.1.11
|View full text |Cite
|
Sign up to set email alerts
|

HER2Ile655Val Single Nucleotide Polymorphism Associated with Early-Onset Breast Cancer Susceptibility: A Systematic Review and Meta-Analysis

Abstract: Breast cancer is the most common cancer among women, with an increasing incidence in most countries, representing a public health threat (Momenimovahed and Salehiniya, 2019;Zahmatkesh et al., 2016). In the United States, breast cancer caused 42,000 deaths in 2017 (Siegel et al., 2020). Clearly, there is a link with ageing, especially among women aged 45 to 65, and it is increasing among younger women (Bouchardy et al., 2007;Dobi et al., 2011;Zubor et al., 2006). Breast cancer under the age of 40 accounts accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Our recent meta-analyses further demonstrate the potential contribution of HER2 Ile655Val single nucleotide polymorphism to the oncogenesis of breast cancer [98]. The meta-analysis showed that the HER2 codon 655 Val allele was significantly associated with an increased risk of breast cancer in an allele genetic model (additive model, RR 1.…”
Section: Her2mentioning
confidence: 52%
“…Our recent meta-analyses further demonstrate the potential contribution of HER2 Ile655Val single nucleotide polymorphism to the oncogenesis of breast cancer [98]. The meta-analysis showed that the HER2 codon 655 Val allele was significantly associated with an increased risk of breast cancer in an allele genetic model (additive model, RR 1.…”
Section: Her2mentioning
confidence: 52%